Level of knowledge about type 2 Diabetes and treatment adherence in honduran population - Galeas Calleja, Norma Isabel (2024)
Introduction: In Honduras, 495,011 people were diagnosed with type 2 Diabetes Mellitus (DMT2) during the year 2015, this being the last existing record, affecting between 7.0% and 10.0% of the population. Diabetes education is essential for adequate control of DM, therefore the purpose of the study was to describe the level of knowledge about Type 2 Diabetes Mellitus and adherence to treatment in the population that attends the National Diabetic Institute in the months of January and February of the year 2023 in Tegucigalpa, Honduras. Methodology: It is a correlational cross-sectional study with a non-experimental approach, with a population of 20,500 patients, a sample of 378 individuals was obtained for analysis. The participants were selected by a non-randomized method, where they answered the Diabetes Knowledge Questionnaire (DKQ 24) to assess the level of knowledge and for adherence to treatment, the Morisky-Green test was used. Results: 266 (70.4%) people had an intermediate level of knowledge and 193 (51.1%) participants, being the majority, reported inadequate adherence to treatment for their disease. When analyzing the relationship between both variables, they have a statistical significance of p 0.007. Conclusions: it is concluded that knowledge about DMT2 should be strengthened among Hondurans, taking into account the areas with deficiency and delve into the factors involved in poor adherence to treatment.